Verifiable outsourced attribute-based encryption with access update - Suqing LIN (网络与信息安全学报)
In order to meet the secure and reliable access requirements for the encrypted data stored in the public cloud,a verifiable outsourced attribute-based encryption scheme with access update was proposed.Based on a standard KP-ABE scheme,verifiable outsourced decryption and verifiable access update for a ciphertext through novel constructions for the scheme were obtained.The verifiability of the outsourced computation ensures that the third-party service may perform algorithms honestly.The scheme has selective IND-CPA security for the original and updated ciphertexts,weak master private key security,and verification soundness in the standard model were proved,respectively.Compared with similar schemes from literatures,the proposed scheme can achieve tradeoff in the optimization of functionality,security and efficiency.